Prediksi Kandungan Kafein Biji Kopi Arabika Gayo dengan Near Infrared Spectroscopy - Rini Rosita; I Wayan Budiastra; Sutrisno - (PERTETA, 2016)
AbstractCaffein is one of the important quality indicator of coffee. Caffein content usually determined by chemical method. Alternative method such Near Infrared Spectroscopy (NIRS) is needed to determine caffein content of coffee rapidly and nondestructively. Applications of NIRS to predict caffein content of coffee were carried out in coffee powders and liquid not in coffee beans. The objective of this study was to assess NIRS method to predict caffein content of arabica coffee bean. Coffee bean samples were placed in petri dish with 2 and 3 layers. The reflectances are measured BY FT-NIR Spectrometer in wavelengths of 1000 – 2500 nm, followed by determination of caffein content by chemical method. Some pre-processing NIRS data such as normalization between 0 and 1 (n01), first derivative of Savitzky-Golay 5 points (dg1), second derivative of Savitzky-Golay 5 points (dg2), combination n01 and dg1, combination n01 and dg2, and PLS calibration to increase accuracy of NIRS prediction. The best prediction is obtained by second derivative and 5 factors PLS with 3 layers of coffee beans with the high R = 0.97 and RPD (5.93), low of SEP and CV (0.007%, 1.76%). This study demonstrated that NIR spectroscopy had excellent potential analysis to determine caffein content of coffee beans.AbstrakKafein merupakan salah satu indikator mutu terpenting dari kopi. Biasanya kandungan kafein kopi ditentukan dengan metoda kimia. Metoda alternatif seperti Near Infrared Spectroscopy (NIRS) diperlukan untuk penentuan kandungan kafein biji kopi secara cepat dan nondestruktif. Hingga saat ini, aplikasi NIRS untuk penentuan kandungan kafein dilakukan pada kopi bubuk atau kopi cair dan bukan pada biji kopi. Tujuan penelitian ini adalah mengkaji metoda NIRS untuk memprediksi kandungan kafein biji kopi arabika gayo. Biji kopi diletakkan dalam cawan petri dengan 2 dan 3 tumpukan. Reflektan biji kopi diukur menggunakan FT-NIR Spectrometer pada panjang gelombang 1000 – 2500 nm. Dilanjutkan dengan penentuan kandungan kafein kopi dengan metode kimia. Beberapa pra-pengolahan data NIRS seperti normalisasi antara 0 – 1 (n01), derivatif pertama Savitzky-Golay 5 point (dg1), derivatif kedua SavitzkyGolay 5 point (dg2), kombinasi n01 dan dg1, dan kombinasi n02 dan dg2 serta kalibrasi dengan PLS dilakukan untuk meningkatkan akurasi metoda NIRS. Prediksi NIRS terbaik diperoleh dengan pra-PLS dengan 3 tumpukan dengan koefisien korelasi (R = 0.97) dan RPD (5.93) yang tinggi, SEP dan CV yang rendah (0.007%, 1.76%). Penelitian ini membuktikan metode NIRS berpotensi untuk analisis kandungan kafein biji kopi.